Changes in liver acceptance patterns after implementation of Share 35. Issue 2 (February 2016) - Washburn, Kenneth; Harper, Ann; Baker, Timothy; Edwards, Erick
Abstract : The Share 35 policy was implemented June 2013. We sought to evaluate liver offer acceptance patterns of centers under this policy. We compared three 1‐year eras (1, 2, and 3) before and 1 era (4) after the implementation date of the Share 35 policy (June 18, 2013). We evaluated all offers for liver‐only recipients including only those offers for livers that were ultimately transplanted. Logistic regression was used to develop a liver acceptance model. In era 3, there were 4809 offers for Model for End‐Stage Liver Disease (MELD) score ≥ 35 patients with 1071 acceptances (22.3%) and 10, 141 offers and 1652 acceptances (16.3%) in era 4 ( P  < 0.001). In era 3, there were 42, 954 offers for MELD score < 35 patients with 4181 acceptances (9.7%) and 44, 137 offers and 3882 acceptances (8.8%) in era 4 ( P  < 0.001). The lower acceptance rate persisted across all United Network for Organ Sharing regions and was significantly less in regions 2, 3, 4, 5, and 7. Mean donor risk index was the same (1.3) for all eras for MELD scores ≥ 35 acceptances and the same (1.4) for MELD score < 35 acceptances. Refusal reasons did not vary throughout the eras. The adjusted odds ratio of accepting a liver for a MELD score of 35+ compared to a MELD score < 35 patient was 1.289 before the policy and 0.960 after policy implementation. In conclusion, the Share 35 policy has resulted in more offers to patients with MELD scores ≥ 35. Overall acceptance rates were significantly less compared to the same patient group before the policy implementation. Centers are less likely to accept a liver for a patient with a MELD score of 35+ after the policy change. Decreased donor acceptance rates could reflect more programmatic selectivity and ongoing donor and recipient matching. Liver Transpl 22:171‐177, 2016 . © 2015 AASLD.